Expression and production optimization of the cationic antimicrobial peptide - indolicidin by the recombinant E. coli C41 (DE3) clones - Selvam, Kanesan Panneer; Nambirajan, Guruvu; Annamalai, Balasubramaniam; Alaidarous, Mohammed; Alshehri, Bader Mohammed; Bin Dukhyil, Abdul Aziz A.; Shobana, Coimbatore Subramanian; Manikandan, Palanisamy (Acta Biologica Szegediensis, 2018)
The cytoplasmic granules of bovine neutrophils naturally possess indolicidin - a promising cationic antimicrobial peptide as it displays inherent inhibitory activities against a broad type of microbial pathogens. In this study, a shake flask level production and expression optimizations of the indolicidin by the recombinant Escherichia coli C41 (DE3) clones (transformed with pET21a(+) plasmid carrying indolicidin gene) were carried out under standard conditions, as to determine the conditions required for maximal production. It was determined that a concentration of 1 mM of IPTG was effective, the 2×YT with salts and LB media at pH 7.5 with 3-6 h of incubation were required for maximal indolicidin expression.